2016
DOI: 10.14814/phy2.12901
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes of arterial oxygen saturation and erythropoietin concentration in male and female highlanders

Abstract: In Caucasians and Native Americans living at altitude, hemoglobin mass is increased in spite of erythropoietin concentrations ([Epo]) not markedly differing from sea level values. We hypothesized that a nocturnal decrease of arterial oxygen saturation (SaO2) causes a temporary rise of [Epo] not detected by morning measurements. SaO2 (continuous, finger oximeter) and [Epo] (ELISA, every 4 h) were determined in young highlanders (altitude 2600 m) during 24 h of usual daily activity. In Series I (six male, nine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
4
13
0
3
Order By: Relevance
“…The finding that the five‐day application did not have a greater EPO response than the single dose may be related to the timing of CO‐ingestion and the diurnal changes in plasma [EPO] . Under baseline conditions, we found circadian fluctuations of plasma [EPO], with low values in the morning and higher values in the afternoon and during the night as described in the literature . It should be noted that the placebo group demonstrated the most pronounce diurnal variation.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The finding that the five‐day application did not have a greater EPO response than the single dose may be related to the timing of CO‐ingestion and the diurnal changes in plasma [EPO] . Under baseline conditions, we found circadian fluctuations of plasma [EPO], with low values in the morning and higher values in the afternoon and during the night as described in the literature . It should be noted that the placebo group demonstrated the most pronounce diurnal variation.…”
Section: Discussionsupporting
confidence: 71%
“…30 Under baseline conditions, we found circadian fluctuations of plasma [EPO], with low values in the morning and higher values in the afternoon and during the night as described in the literature. 31,32 It should be noted that the placebo group demonstrated the most pronounce diurnal variation. Since subjects were randomly assigned to treatment groups it is unlikely that selection bias contrib- During the day, when Co 2+ has been administered every 4 hours, continuous stimulation occurs in the 10 mg group, with higher EPO values in the afternoon (at 2 pm) and at night (at 9 pm, Figure 3D).…”
Section: Cobalt Excretion In Urinementioning
confidence: 99%
“…While the study in Uppsala was performed at an elevation of about 15 m above sea level, Cristancho et al reported EPO rhythms in men and women living at least 3 years in of Bogotá, Columbia, with an elevation more than 2600 m over sea level. EPO peaked in both genders late in the night around 4 a.m. [136]. While these studies provide potential evidence that the rhythm of circulating EPO may change at different elevations, more studies involving different populations at varying elevations are necessary to confirm these findings.…”
Section: Integration Of Circadian Control Throughout the Nephronmentioning
confidence: 99%
“…Başka bir deyişle, sirkadiyen ritme bağlı olarak tüm vücut fonksiyonları da gün içi ya da diurnal değişkenlikler ve salınımlar içerisindedir (Atkinson & Reilly 1996;Reilly, Atkinson & Waterhouse 1997;Rosa 2016). Bu bağlamda, diurnal ya da gün içi salınımların sportif performans düzeyi üzerinde de etkili olduğunu ve birçok fiziksel performans bileşeninin gün içerisinde değişkenlik sergilediğini gösteren çok sayıda bilimsel araştırma bulunmaktadır (Atkinson & Reilly 1996;Reilly, Atkinson & Waterhouse 1997;Reilly 2009;Rossi 2015;Thun 2015;Cristancho 2016;Ghattassi 2016;Rosa 2016).…”
unclassified
“…Ancak literatürde yer alan biyolojik ritimlerle, özellikle de sirkadiyen ritimle ilgili olarak, diurnal değişkenliklerin sportif performans bileşenleri üzerindeki etkilerini inceleyen çok sayıdaki çalışmada, farklı yüklenme yöntemlerine verilen yanıtlardaki değişimler ele alınmıştır. Diğer bir deyişle, kronobiyolojik çalışmalar yüklenmeye verilen yanıtlardaki değişkenlikler üzerinde odaklanmıştır (Hill & Smith1991;Atkinson & Reilly 1996;Reilly, Atkinson & Waterhouse 1997;Deschodt & Arsac 2004;Souissi 2004;Nicolas 2008;Reilly 2009;Rossi 2015;Thun 2015;Cristancho 2016;Ghattassi 2016;Hatfield, Nicoll & Kraemer 2016;Rosa 2016). Yüklenme sonrası toparlanma sürecine ilişkin olarak diurnal değişimlerin incelendiği bilimsel araştırma sayısı ise oldukça azdır (Güneş 1998;Güvenç 2004;Nicolas 2007;Waterhouse 2007;Morris 2009).…”
unclassified